Paisagens ambulantes: as apropriações efêmeras na região da 44 em Goiânia - Silva, Camila Borges da (2020)
This work sought to study how the ephemeral appropriation of the 44 region in Goiânia creates a ‘wandering landscape’. Each city has its own characteristic dynamics, making it unique. This dynamic is framed by the way people inhabit the urban space, the way in which they establish social relations, and the way in which they appropriate and network relations of exchange and trade. The commercial centralities concentrate formal workers, consumers and also informal street vendors, popularly known in Brazil as “ambulantes”. With the growing unemployment in Brazil, the informal market has become an increasingly alternative way of survival. They take ownership of the city and urban space, as a way of exercising the right to the city and employment, becoming active agents in the transformation of space and the urban landscape. The object of study is the 44 region in the city of Goiânia, consolidated as a clothing commercial centre since 2000, which has been attracting businessmen, workers, shopping tourists and street vendors since then. Different categories of street vendors take over the urban space of the region, changing the dynamics and the local landscape, in search of their own livelihood. This is an act that divides opinions, being seen as a way of exercising the right to work, but also as an illegal form of this exercise. This research discusses the different types of street vendors present in the region, categorizing them based on the structures they use. These types was divided into two categories, the circulable and the effective moving points. We describe the way they take over the urban space and how they transform the local urban landscape, understanding it as mobile landscapes. The methods adopted was: spatial perception and ethnographic techniques , which made it possible to understand the way in which street vendors appropriate the urban space; the taxonomic exercise, which made a 'critical' classification of the categories of street vendors, through the structures used and the products sold; and the cartographic exercise, which resulted in the psychogeographic mapping of the way they appropriate the urban space. Finally, the findings obtained with these methodologies made it possible to explore concepts to clarify the dynamics and paradoxes of this wandering landscape. In addition, this work brings a new look at still little studied city agents, the street vendors, which enabled a new form of understanding its relation to the city, which can guide and be used in future investigations.